Healthcare costs at the end-of-life among immigrant and non-immigrant groups in Manitoba, Canada - Debbarman, Shantanu; Witt, Julia; Oguzoglu, Umut; Urquia, Marcelo L. (International Journal of Population Data Science, 2024)
Objectives It is known that healthcare costs tend to increase during the last year of life. Recognizing the importance of efficient resource distribution for end-of-life care, this study compares healthcare costs incurred for migrants and long-term Manitobans and identifies the factors that impact healthcare costs during the last year of life. Methods This retrospective matched-cohort study used 15 databases linked at the individual-level, including immigration records, medical claims, hospital abstracts, drug prescriptions, emergency department visits, home care, long-term care, vital statistics mortality, housing and employment/income assistance, for those who died between January 2005 and December 2022 in Manitoba. Conditional zero-inflated gamma hurdle (ZIG) and quantile regression models were used. Results The average end-of-life healthcare costs for international migrants (2469) and Long-term Manitobans (2362) were CA44,909 and CA16,593, respectively. According to the adjusted ZIG model, international migrants had 17% higher costs. Among international migrants, Government Assisted and Blended Visa Office-Referred Refugees (GAR/BVOR) had 36% higher costs than Long-term Manitobans. Additionally, costs were higher for those without a partner (13%), receiving employment/income assistance (30%), having higher comorbidity (309% for 4+ comorbidities vs. 0 comorbidities), death at the hospital (171%), and long-term care (169%). Adjusted Quantile regression analyses revealed that only GAR/BVOR had higher costs across all levels of the cost distribution than long-term Manitobans. Conclusion In the last year of life, international migrants incurred greater healthcare costs than non-immigrants. However, the differences with non-immigrants varied depending on international migrants’ characteristics.